1996
DOI: 10.1590/s0101-81751996000300002
|View full text |Cite
|
Sign up to set email alerts
|

The species of Hippolyte Leach (Crustacea, Caridea, Hippolytidae) from Terminos Lagoon, southwestern Gulf of Mexico

Abstract: ABSTRACT. The taxonomic idenlity 01' specilllcns 01' lhe genus Hippolyte Lcach, 1814 01' Laguna de Términos was considered including the colour and lhe presenceabsence oftufts ofplumose seta e on the dorsal surl;\ce ofthe. ca rapace and abdomen as secondary characteristics to 1ll0rph o log icall1~at ure.s oflaxonomic va i ue. Two groups were formed based on appearance: one lransparenl with setae and another green without setae. The analys is of tive morphol ogical characteri sti cs in adult females of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
3
9
0
1
Order By: Relevance
“…A relação do logaritmo do número de ovos postos por fêmea em função do comprimento cefalotorácico está representada na Fig. 3, a Tal fato ocorre em outros carídeos como o Macrobrachium carcinus, M. potiuna, M. acanthurus e Hippolyte zostericola estudados, respectivamente, por Lobão et al (1985), Bond & Buckup (1982), Valenti et al (1989) e Negreiros-Fransozo et al (1996. Clarke (1993) afirma que o tamanho dos ovos dos invertebrados aquáticos varia amplamente, refletindo uma variação do investimento pela fêmea em cada embrião e as fêmeas menores desovam menor número de ovos, por apresentarem um ovário menor e um reduzido espaço no abdome para a incubação dos mesmos.…”
Section: Resultsunclassified
“…A relação do logaritmo do número de ovos postos por fêmea em função do comprimento cefalotorácico está representada na Fig. 3, a Tal fato ocorre em outros carídeos como o Macrobrachium carcinus, M. potiuna, M. acanthurus e Hippolyte zostericola estudados, respectivamente, por Lobão et al (1985), Bond & Buckup (1982), Valenti et al (1989) e Negreiros-Fransozo et al (1996. Clarke (1993) afirma que o tamanho dos ovos dos invertebrados aquáticos varia amplamente, refletindo uma variação do investimento pela fêmea em cada embrião e as fêmeas menores desovam menor número de ovos, por apresentarem um ovário menor e um reduzido espaço no abdome para a incubação dos mesmos.…”
Section: Resultsunclassified
“…Relationship between #E produced and CL was positive for females. According with Berglund and Rosenqvist (1986), this is a pattern observed in several crustaceans; in carideans Hippolyte zostericola (Negreiros-Fransozo et al, 1996), Synalpheus filidigitus (Duffy & Macdonald, 1999), possess this reproductive characteristic. The best fit of our data on the variation of #E vs. CL for T. carolinense females was the quadratic equation.…”
Section: Datementioning
confidence: 78%
“…Historically, the presence of this characteristic was considered as a unique character of the genus Hippolyte (Lebour 1931;Gurney 1937;Lebour 1940;Williamson 1957). Nevertheless, more recent studies of first zoeal stage of this genus revealed that four species (H. acuta, H. pleuracanthus, H. williamsi and H. zostericola) did not show this seta (Yokoya 1957;Shield 1978;Albornoz & Wehrtmann 1997;Negreiros-Fransozo et al 1996;respectively). The presence of this exopodal seta in the maxillule of Zoea I has been reported also from other members of the family Hippolytidae: Alope spinifrons (Packer 1985), Thor novaezealandiae (Packer 1985) and species from the genus Nauticaris (Packer 1985;Wehrtmann & Albornoz 1998) as well as from other caridean shrimps (Gurney 1942;Haynes 1985) Therefore, this character cannot be used to separate the first zoeal stage of representatives of Hippolyte from those of other hippolytid and caridean shrimps.…”
Section: Discussionmentioning
confidence: 98%
“…The larval morphology of the family Hippolytidae or some hippolytid genera has been reviewed by several authors (Lebour 1932;Gurney 1937;Gurney 1942;Haynes 1985 Dana and H. nicholsoni Chace). The first zoeal stage was studied in five of these species: H. clarkii (by Needler 1934 as Hippolyte californiensis), H. coerulescens (by Gurney 1936as H. acuminata), H. pleuracanthus (by Shield 1978, H. williamsi (by Albornoz & Wehrtmann 1997) and H. zostericola (by Negreiros-Fransozo et al 1996). However, except for H. pleuracanthus, the other descriptions of the first zoeal stage were incomplete, since many structures were not cited or described in detail.…”
Section: Introductionmentioning
confidence: 99%